2016
DOI: 10.1111/ijlh.12474
|View full text |Cite
|
Sign up to set email alerts
|

Association of mean platelet volume and platelet count with the development and prognosis of ischemic and hemorrhagic stroke

Abstract: Increased MPV is an independent risk factor for both strokes. Elevated PLT count increases the risk for ischemic stroke, but decreases the risk for hemorrhagic stroke. However, neither MPV nor PLT count has significant association with the prognosis of either stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 26 publications
5
67
1
Order By: Relevance
“…Further, a retrospective study by Lok et al (17) in 2017 which 798 first time acute ischemic stroke patients participated, showed that MPV values were not associated with short-term stroke prognosis and neurological functions. Also, a study compared MPV values of 281 first-episode acute ischemic stroke and 164 first-episode hemorrhagic stroke patients and found that MPV values were high in both groups but it is not associated with the prognosis (5). In contrast, in a 2017 study conducted on 100 acute cerebral infarction patients and 80 healthy controls by Wan and Ma (18), it was found that MPV values were high in the patient group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, a retrospective study by Lok et al (17) in 2017 which 798 first time acute ischemic stroke patients participated, showed that MPV values were not associated with short-term stroke prognosis and neurological functions. Also, a study compared MPV values of 281 first-episode acute ischemic stroke and 164 first-episode hemorrhagic stroke patients and found that MPV values were high in both groups but it is not associated with the prognosis (5). In contrast, in a 2017 study conducted on 100 acute cerebral infarction patients and 80 healthy controls by Wan and Ma (18), it was found that MPV values were high in the patient group.…”
Section: Discussionmentioning
confidence: 97%
“…Platelets are involved in hemostasis, thrombosis and coagulation processes. Circulating platelets are heterogeneous in size, density, and reactivity, and large platelets are more active metabolically and enzymatically (5). Large platelets produce a greater number of prothrombotic factors such as β-thromboglobulin, thromboxane B2, serotonin, glycoprotein IIIA, and P-selectin, and they are more prone to aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that each of these indicators is a predictor of stroke prognosis [7,9,27,28]. Further, serum albumin and hemoglobin concentration have predictive value for stroke recurrence and combined events [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of NVG secondary to RVO or DR is multifactorial and remains unknown. It has been shown that platelets play an important role in the pathophysiology of retinal artery occlusion [27], nonarteritic anterior ischemic optic neuropathy [6], ischemic and hemorrhagic stroke [7], and cardiovascular diseases [28]. In this study, 38 patients with NVG secondary to RVO and 47 patients with NVG secondary to DR were studied with regard to platelet parameters and compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets play an important role in the pathogenesis of various thrombo-occlusive diseases, such as anterior ischemic optic neuropathy [6], ischemic and hemorrhagic stroke [7], and RVO [8]. Mean platelet volume (MPV) is a major indicator of the production rate and size of platelets, and has been associated with the activities of platelets [9, 10].…”
Section: Introductionmentioning
confidence: 99%